Βιβλιοκρισία: Late Byzantium Reconsidered. The Arts of the Palaiologan Era in the Mediterranean Edited by Andrea Mattiello and Maria Alessia Rossi, London and New York 2019 - ΔΡΑΚΟΠΟΥΛΟΥ, Ευγενία (Byzantina Symmeikta, 2020)
Βιβλιοκρισία: Late Byzantium Reconsidered. The Arts of the Palaiologan Era in the Mediterranean Edited by Andrea Mattiello and Maria Alessia Rossi, London and New York 2019